INTEGRATING SPIRITUAL VALUES INTO ONLINE COMPETITION PLATFORMS TO ENHANCE STUDENTS’ ACHIEVEMENT IN ECONOMICS OLYMPIAD: A BEST PRACTICE STUDY - Muhammad Putra Aprullah; Muhammad Sayuthi; Salsabilla Julnadi; William Ben Gunawan; Indrayani Indrayani; Raida Fuadi; Zahara Zahara; Agus Adria (Institut Pendidikan Tapanuli Selatan, 2026)
This study aims to examine best practices for integrating spiritual values into an online competition website to improve students’ achievement in the Economics Science Olympiad at MAN 1 Banda Aceh. This study employed a descriptive, qualitative approach with a best-practices design. Data collection was conducted through observation, in-depth interviews, and documentation involving the principal, supervising teachers, and student participants in the Olympiad program. The results indicate that the integration of spiritual values was systematically implemented through three interconnected stages: the pre-competition stage (intention formation, spiritual and mental readiness), the competition stage (emotional control, trust in God, and stress management), and the post-competition stage (reflection, gratitude, and character building). This integrative approach has been proven not only to improve students’ cognitive achievement at the city, provincial, and national levels but also to strengthen affective and psychomotor aspects, such as self-regulation, mental resilience, digital literacy, and ethical competitive attitudes. This study confirms that the effectiveness of the online competition website is maximized when integrated into a holistic educational framework grounded in spiritual values. These findings contribute to the development of literature on digital learning, character education, and contemporary Islamic education.